Dumping Dalam Perspektif Hukum Perdagangan Internasional - Dandy Rezky Sanjaya; Muh. Hartato S. Hadi; Supriyadi Supriyadi (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study aims to analyse anti-dumping regulations in international trade and their application to the domestic industry of imported products with indications of dumping. The research method used is the normative legal research method. The results of his research are that apart from referring to international regulations (Agreement on Implementation of Article VI GATT and the Agreement on Subsidies and Countervailing Duties), they also refer to national laws and regulations, namely laws. No. 10 of 1995 concerning Customs. Anti-dumping regulations are urgently needed to protect domestic industries against practices that can harm domestic industries that produce similar goods. Applications that Indonesia can carry out to overcome dumping practices must first be carried out by an investigation by KADI to obtain evidence regarding imported products with indications of dumping, which will be detrimental to the domestic industry. According to this evidence, through KADI, the government can charge importers anti-dumping import duties.